Cost efficiency of district heating for low energy buildings of the future. (15th June 2019) - Hansen, C.H.; Gudmundsson, O.; Detlefsen, N.
Abstract: Projects like the 4DH research platform and Heat Roadmap Europe have successfully demonstrated that district heating is the only viable solution to efficiently utilize both low-grade renewable energy, excess heat from other sources as well as waste heat for providing heat for space heating and domestic hot water purposes. Nevertheless, there are open questions regarding cost competitiveness of district heating in combination with low energy buildings of the future. In fact, one of the challenges district heating is facing, is the general perception that district heating is too investment intensive compared to individual solutions. In many cases that perception is also used to imply that district heating has no future with the introduction of strict building energy codes that require new buildings to fulfill low energy buildings standards. In this paper, the levelized cost of heating using district heating and individual heating solutions are compared by looking at a concrete area where both the heat demand per square meter as well as the distance between buildings are varied. This study thus analyses when a 4th generation district heating system is competitive, under different linear heat densities.